Clinico-Therapeutic Management of Impacted Colic in a Donkey - Ajabe, JS; Siddqui, MFMF; Shaikh, SR (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Colic is defined as pain originated from the gastro-intestinal tract. It causes the most serious condition in horses and donkeys, which result in severe abdominal pain and discomfort (Radostits et al., 2007).